2020
DOI: 10.2147/ott.s217087
|View full text |Cite
|
Sign up to set email alerts
|

<p>HIPK3 Promotes Growth and Metastasis of Esophageal Squamous Cell Carcinoma via Regulation of miR-599/c-MYC Axis</p>

Abstract: Background/Aims: this experimental design was based on HIPK3 to explore the pathogenesis of ESCC. Methods: RT-qPCR was used to detect the expression of CircHIPK3 and miR-599 in ESCC tissues and cell lines.CCK-8, colony formation, flow cytometry and transwell assay were used to detect the effects of CircHIPK3 and miR-599 on tumor cell proliferation, apoptosis and migration and invasion. Target gene prediction and screening, luciferase reporter assays were used to validate downstream target genes of CircHIPK3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The metastasis of osteosarcoma cells is mediated through the circHIPK3-miR-637/STAT3 signaling pathway ( 46 , 47 ). In animal experiments, circHIPK3 promoted the proliferation and metastasis of esophageal squamous cell carcinoma cells by mediating the circHIPK3-miR-599/c-MYC signaling pathway ( 48 ).…”
Section: Circhipk3 Biogenesismentioning
confidence: 99%
“…The metastasis of osteosarcoma cells is mediated through the circHIPK3-miR-637/STAT3 signaling pathway ( 46 , 47 ). In animal experiments, circHIPK3 promoted the proliferation and metastasis of esophageal squamous cell carcinoma cells by mediating the circHIPK3-miR-599/c-MYC signaling pathway ( 48 ).…”
Section: Circhipk3 Biogenesismentioning
confidence: 99%
“…Meanwhile, MiR150 was closely related to the metastasis of nasopharyngeal carcinoma [ 183 ]. Circ RNAs Circ_0008035 miR-599/EIF4A1 [ 104 ] miR599/c-Myc [ 184 ] Circ_0008035 was increased in GC tissues to suppress ferroptosis via miR-599/EIF4A1 axis [ 104 ]. Additionally, miR599/c-Myc pathway was also involved in the metastasis of esophageal squamous cell carcinoma [ 184 ].…”
Section: Pyroptosis In Cancer Metastasismentioning
confidence: 99%
“…Based on the existing literature, we can verify that circRNA hsa_circ_0001649 and circRNA hsa_circ_0001141 are related to liver cancer [ 29 , 30 ]. In addition, a recently published paper showed that circRNA hsa_circ_0000284 promotes gemcitabine sensitivity in bladder cancer [ 31 ] and has also been verified to be related to esophageal cancer via microRNA [ 32 ]. A published study also showed that circRNA hsa_circ_0001141 is associated with esophageal cancer [ 33 ].…”
Section: Resultsmentioning
confidence: 99%